2020
DOI: 10.1007/s00330-020-07375-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of image quality related reference doses called acceptable quality doses (AQD) in paediatric CT exams in Qatar

Abstract: Objectives To describe first experience of integrating assessment of image quality in paediatric X-ray computed tomography (CT) with analysis of the radiation dose indices to develop reference doses called acceptable quality dose (AQD). Methods Image quality was scored by the radiologists at a tertiary care hospital in Qatar on a scale of 0 to 4 using the recently published scoring criteria. The patients undergoing head, chest and abdomen CT were divided in different weight groups as follows: < 5 kg, 5–&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Is has been suggested that image quality should be part of the DRL system and a so-called acceptable quality doses should be derived. 15 This system was later clinically used and evaluated 16 using image quality scoring criteria developed for paediatric CT. 17 With this approach, doses from patient examinations with suboptimal image quality are excluded before the typical values are derived.…”
Section: Discussionmentioning
confidence: 99%
“…Is has been suggested that image quality should be part of the DRL system and a so-called acceptable quality doses should be derived. 15 This system was later clinically used and evaluated 16 using image quality scoring criteria developed for paediatric CT. 17 With this approach, doses from patient examinations with suboptimal image quality are excluded before the typical values are derived.…”
Section: Discussionmentioning
confidence: 99%
“…For standard procedures, it is not anticipated that these levels will be exceeded when good and conventional practice in terms of diagnostic and technical performance are used [7]. DRL methods are advisory practices and remain opposed to the dose-limit concept and it aims to minimise radiation doses to patients to acquire optimum image quality [22,23]. DRL can be performed at three levels: local DRL (LDRL), national DRL (NDRL), or regional (RDRL) [7,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The 5-star rating for image quality (Tables 1 and 2) differs from previous linear, 3-point scoring for noise and acceptable spatial resolution (optimum; too much; too little) and 4-point scoring for diagnostic acceptability (1: fully acceptable; 2: probably acceptable; 3: acceptable only for limited conditions; 4: unacceptable) such as the one proposed as European Quality Criteria [10]. Conversion of a point scale to a 5-star rating goes with the intent of recent publications [6,7]. The non-linear 5-star rating of diagnostic quality rewards top rating to the clinical indication-based personalized protocols with "just adequate" diagnostic quality and, by extension, radiation doses such as low-dose CT for nodule follow-up, kidney stone evaluation, or paranasal sinus CT before an endoscopic surgery.…”
mentioning
confidence: 99%
“…The situation calls for a black box, artificial intelligence (AI) models to take over the task of selecting the right dose for the right quality [5]. While that may be thought for future, recent studies have used subjective assessment on an institutional level so as to have an acceptable quality dose (AQD) [6,7]. AQD can be personalized to body habitus, body region, scanner type, clinical indication, and quality and dose requirements.…”
mentioning
confidence: 99%